(untitled) (Research, Society and Development, 2021)
The quest for telework by organizations, especially motivated by the pandemic in 2020, caused many difficulties to arise regarding its implementation in an adequate and structured way. The objective of this research is to identify the approaches and strategies on the implementation of telework, especially through roadmaps. Based on the theory available in the international literature on telework, we sought to present the terms and concepts that refer to the universe of this type of work. The method of systematic literature review was used, whose protocol was adopted as the PRISMA-P. No roadmap proposal was found that could serve as a strategic roadmap for the implementation of teleworking in organizations. The results show the relevance of this theme in the world, and its advantages and disadvantages are the most present approach in research.